Metabolic Seizures - Almannai, Mohammed; Al Mahmoud, Rabah A.; Mekki, Mohammed; El-Hattab, Ayman W. (Frontiers in Neurology, 2021)
Metabolic diseases should always be considered when evaluating children presenting with seizures. This is because many metabolic disorders are potentially treatable and seizure control can be achieved when these diseases are appropriately treated. Seizures caused by underlying metabolic diseases (metabolic seizures) should be particularly considered in unexplained neonatal seizures, refractory seizures, seizures related to fasting or food intake, seizures associated with other systemic or neurologic features, parental consanguinity, and family history of epilepsy. Metabolic seizures can be caused by various amino acids metabolic disorders, disorders of energy metabolism, cofactor-related metabolic diseases, purine and pyrimidine metabolic diseases, congenital disorders of glycosylation, and lysosomal and peroxisomal disorders. Diagnosing metabolic seizures without delay is essential because the immediate initiation of appropriate therapy for many metabolic diseases can prevent or minimize complications.